Application of Polyalphabetic Substitution Cipher using Genetic Algorithm - Ghusoon Basheer (Al-Rafidain Journal of Computer Sciences and Mathematics)
Several Genetic Algorithms have been developed for applications of cryptography problem; the primary distinction among all of them being the G.A. used for decryption problem and obtains the plain text. In this paper a new approach is proposed using Genetic Algorithm with cryptography. G.A. is used to obtain a best secret key in polyalphabetic substitution cipher. This key will be used then for encryption and decryption with a high level of security. The program is written in Matlab language (6.5).